Synthesis and recognition properties of calix[4]arene semitubes as ditopic hosts for N-alkylpyridinium ion pairs. Issue 26 (10th May 2016) - Vita, Francesco; Vorti, Michela; Orlandini, Guido; Zanichelli, Valeria; Massera, Chiara; Ugozzoli, Franco; Arduini, Arturo; Secchi, Andrea
Abstract : Three novel calix[4]arene semitubes having two alkyl bridging spacers of different lengths were synthesized and used as homoditopic hosts for small neutral acidic molecules and N -alkylpyridinium salts. Abstract : A series of calix[4]arene semitubes (4a–c ) having alkyl bridging spacers of different lengths and flexibilities on their lower rim was synthesised and characterised in solution and in the solid state by 1 H NMR spectroscopy and X-ray crystallography. The binding properties of these novel ditopic hosts toward a series of N -alkylpyridinium ion pairs were investigated in low polar media by 1 H NMR and UV-vis spectroscopy and compared with those of the corresponding calix[4]arene monotopic host5 . These studies showed that in low polar solvents, the calix[4]arene semitubes behave as homoditopic hosts giving rise with N -alkylpyridinium ion pairs to supramolecular adducts of 1 : 2 host–guest stoichiometry.